A web-based system for the selection of characteristic ground motions. (September 2019) - Klinc, Robert; Šebenik, Žiga; Dolšek, Matjaž; Brozovič, Marko; Dolenc, Matevž
Highlights: A web-based system (CGMapp) for the selection of characteristic ground motions (CGMs) is introduced. CGMs are risk-targeted, hazard-consistent and structure-specific ground motions. CGMapp facilitates the use of nonlinear dynamic analysis in earthquake engineering. CGMapp is a research tool which can be further developed aimed at extending its possibilities for ground motion selection. Abstract: In the paper a web-based system CGMapp for the selection of characteristic ground motions is presented. It performs the selection of ground motions according to the conditional spectrum approach by considering the old PEER and RESORCE databases, and refines this selection by making use of nonlinear dynamic analyses of a single-degree-of-freedom (SDOF) model, so that seven characteristic ground motions are obtained. They can be understood as risk-targeted, hazard-consistent, and structure-specific ground motions, which can be used within the scope of the 3R method (Record selection, Response analysis and Risk-based decision making) in order to make decisions about the collapse safety of symmetric buildings, by performing only a few nonlinear response history analyses. It was shown by the proposed web-based system that the automation of the selection of the characteristic ground motions is possible through the internet. Thus, the use of the 3R method becomes trivial, so that the researcher will have the possibility to test the method, which will help to better understand the range of applicability of the proposed 3R method. In the paper, the background of CGMapp is first explained. This is followed by a demonstration of the use of the presented web-based system for the selection of characteristic ground motions in the assessment of the collapse safety of an 8-storey reinforced concrete dual structure. Although only seven nonlinear dynamic analyses were performed using characteristic ground motions, it is shown that the decision about collapse safety was the same as that obtained on the basis of incremental dynamic analysis, which requires hundreds of simulations. Finally, it is also shown that the web-based system can be used as a research tool, in order to obtain a better understanding of the impact of the uncertainty of the selection of ground motions on decision-making in earthquake engineering.